POPULISMUS - Kontroversen und Perspektiven Ein wissenschaftliches Gesprächsangebot - Fleck, Marina; Hirschmüller, Tobias; Hoffmann, Thomas (Akademische Verlagsgemeinschaft München (AVM), 2020)
Hardly any other term has been discussed as often and controversially in recent years as "populism". The conflict already begins with the search for a valid definition, because this endeavor often ends in mutual accusations, even among scholars, of being populist themselves. On the one hand, the term is used to accuse the political "opponent" of a distorted and simplified way of reasoning. At the same time, it is used as an inflationary killer argument to discredit the opponent when no constructive and valid counterarguments can be presented. Thus, it is ultimately an often unspecifically used buzzword, whose use can range from describing a form of political rhetoric to denouncing racist and anti-democratic worldviews. This volume therefore seeks to address this phenomenon in an interdisciplinary manner, approaching it from historical and political perspectives, as well as from linguistic and theological perspectives. Here, too, no absolute answers can be provided, but ultimately only a scholarly offer for discussion - anything else would be populism.